2011
DOI: 10.11120/ital.2011.10030068
|View full text |Cite
|
Sign up to set email alerts
|

What Students are Telling us about Why They Left Their ICT Course

Abstract: Student attrition is an issue of particular concern in the field of ICT because the industry faces staffing shortfalls. The study described in this paper provides further understanding of the causes of attrition from ICT courses by exploring the reasons students give for leaving their ICT courses. An online survey of early leavers from four Australian universities was conducted. The results show that many factors can contribute to the attrition of ICT students, and that for many students it is a combination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Underrepresentation in computing is a public concern, affecting the availability of an adequate, stable computing workforce, global competitiveness, defense, health, national security, and social justice. Women in CS leave the major more frequently than men despite their high performance [6,19,31,33].…”
Section: Introductionmentioning
confidence: 99%
“…Underrepresentation in computing is a public concern, affecting the availability of an adequate, stable computing workforce, global competitiveness, defense, health, national security, and social justice. Women in CS leave the major more frequently than men despite their high performance [6,19,31,33].…”
Section: Introductionmentioning
confidence: 99%
“…The primary complaint by students was that classes were boring, and lacked a real-world or workplace focus. 2,3,4 Students also complained about poor teaching, 2 and teaching at too fast a pace. In addition, many students felt that they lacked suitable preparation through prior experience, particularly in programming skills and database concepts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, many students felt that they lacked suitable preparation through prior experience, particularly in programming skills and database concepts. 2,3,5,6 A few studies found that the students' ability to integrate into the academic and social environment of the university played an important role in retention. 3 The most important factor in this integration was building a peer group support system through peer interaction in the classroom.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…29,30 A limitation of this study was conducting research with a small sample size. This could show slight inaccuracies with the results in comparison to findings from similar studies.…”
mentioning
confidence: 99%